THE SIGNIFICANCE OF FEMALE IMAGERY IN RUSSIAN AND UZBEK POETRY (Web of Teachers: Inderscience Research, 2024)
This article examines the significance of female images in Russian and Uzbek poetry and compares the cultural, historical and social aspects that form women's images in these literatures. By analyzing classical and contemporary poems, the study sheds light on how female figures are depicted, their symbolic roles, and the evolution of their depiction over time. The study examines works drawn from both poetic traditions, identifies key differences and similarities, and provides insight into how these images reflect broader social attitudes toward women.